Cover Image. Issue 6 (24th May 2021) - Yibeltal, Mesenbet; Tsunekawa, Atsushi; Haregeweyn, Nigussie; Adgo, Enyew; Meshesha, Derege Tsegaye; Masunaga, Tsugiyuki; Tsubo, Mitsuru; Billi, Paolo; Ebabu, Kindiye; Liyew Berihun, Mulatu
Abstract : The cover image is based on the Original Article Effect of subsurface water level on gully headcut retreat in tropical highlands of Ethiopia by Mesenbet Sebhat et al., https://doi.org/10.1002/esp.5095 .